Experimental properties of bonded soils - Bressani, Luiz Antonio (1990)
The properties of weakly bonded soil have been studied experimentally, mainly by an extension of recent work on artificial bonded sand. Higher stresses were used to fully examine yield of this soil when at denser states. Triaxial equipment applying confining pressures of 3.5 MPa and a belt for measuring radial strain on triaxial soil samples were developed. The influence of saturation procedures on test results was investigated. A new loading arrangement has been used and comparative studies carried out to evaluate its influence. The new arrangement improves the stress distribution in the sample and the quality of the conventional strain measurements taken platen to platen. It also reduces premature failure of tbe sample due to non-uniform stresses. Two natural materiais with some degree of cementation were also tested: the Corinth marl (a soft carbonaceous rock from Greece) and the Chemususu Dam soil (a red lateritic soil from Kenya). Both materiais have similar characteristics to the artificial soil when tested in triaxial compression. The bonded soils have shown a characteristic variation of stiffness with confining pressure. As the pressure is increased the secant initial stiffness increases initially but, at some treshold value of confining stress, show stabilization or even a drop on its absolute value, depending on the initial void ratio and the strength of the bonding. The bonded soils have a curved yield locus which is coincident with the failure envelope at low stresses. The failure envelope in the low stress region is dependent of the stress path, being lower for conventional drained compression tests.